The Influence of Soft Skills on Work Readiness Students of the Faculty of Economics and Business State University of Gorontalo - Manhia, Ayisah; Hinelo, Raflin; Taan, Hapsawati (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to determine the effect of soft skills on the work readiness of students at the Faculty of Economics and Business, Gorontalo State University. This study uses a quantitative approach. The population in this study was students of the Faculty of Economics and Business, Gorontalo State University, intakes of 2021 to 2023, with the sample determined using the Slovin formula. The research data used were primary data obtained through distributing questionnaires to 100 respondents using a purposive sampling technique. The data analysis technique used was simple linear analysis with the aid of Statistical Program for Social Science (SPSS 25). The results of this study indicate that soft skills have a positive and significant effect on work readiness. This means that the greater the mastery of students' soft skills, the greater their work readiness in facing the world of work.